Effect of temperature on fast forging process of Mg-Ni samples for fast formation of Mg2Ni for hydrogen storage. (24th January 2020) - Skryabina, Nataliya; Aptukov, Valery; de Rango, Patricia; Fruchart, Daniel
Abstract: Fast-Forging was used as a Severe Plastic Deformation technique to process Mg/Ni fine powder mixtures at a ratio corresponding to the eutectic composition. The samples were processed at different temperature, increased successively from room temperature up to above 500 °C. The one shock forging operation led to a reduction rate comprised between 80 to more than 90% depending of the applied temperature. Interestingly, a threshold temperature was pointed out for which amounts of the binary Mg2 Ni alloy were directly synthesized in increasing proportions when increasing temperature. A maximum amount of Mg2 Ni was synthesized according the nominal proportions at the highest applied temperature. Besides, numerical simulations were developed to consider and integrate to the forging process, the heat arising from the mechanical energy at deformation. Interestingly the total temperature at shock – heat applied to and heat developed in – indicates that the threshold temperature correspond well with the eutectic temperature as reported in the phase diagram. Early hydrogenation cycles suggest that both mechanical defects in brittle Mg and presence of amounts of Mg2 Ni as catalyst should be combined to optimize the hydrogenation characteristics. Highlights: Fast forged Mg-Ni powders forming Mg/Mg2 Ni alloys. Alloying effect versus the effective temperature and the type of particles. Hydrogen uptake versus fast forging conditions.